2020
DOI: 10.3758/s13428-020-01463-8
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Waterless Empirical Taste Test (WETT®)

Abstract: The sense of taste is rarely assessed quantitatively outside of a limited number of academic and industrial laboratories, despite its role in influencing nutrition, the flavor of foods and beverages, and protection against ingestion of spoiled and toxic foodstuffs. This dearth reflects, in part, practical limitations of most taste tests, most notably their reliance on liquid stimuli for stimulus presentation or rinsing. In this study, a novel portable taste test that requires neither liquid tastants nor liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 41 publications
(43 reference statements)
0
28
0
Order By: Relevance
“…The Brief Smell Identification Test (B‐SIT) and the self‐administered version of the Waterless Empirical Taste Test (SA‐WETT®) were mailed, along with instructions for their self‐administration and scoring, to addresses provided by participants on the screening survey 16,17 …”
Section: Methodsmentioning
confidence: 99%
“…The Brief Smell Identification Test (B‐SIT) and the self‐administered version of the Waterless Empirical Taste Test (SA‐WETT®) were mailed, along with instructions for their self‐administration and scoring, to addresses provided by participants on the screening survey 16,17 …”
Section: Methodsmentioning
confidence: 99%
“…We also found that such ability was greater in women than in men, regardless of their cultural background. These phenomena were also evidence in the clinical participants of the validation study of the WETT, where age and gender were significant factors for not only the WETT, but also for two chemically based taste tests (Doty et al, 2021 ). Again, however, the age‐related affect was attenuated for NaCl on all three tests.…”
Section: Discussionmentioning
confidence: 72%
“…The present study compared the performance of a sizable sample of Chinese and American subjects on a recently developed and very reliable taste test that employs, in addition to representatives of the four classic basic taste qualities, umami, a tastant that is more common in Chinese than in American cuisine (Doty, Wylie, & Potter, 2021 ). This test uses taste stimuli embedded in disposable pads of cellulose and has been found to be sensitive to age, sex, phenylthiocarbamide taster status, and head trauma.…”
Section: Introductionmentioning
confidence: 99%
“…The UPSIT contains 40 multiple-choice questions involving the identification of microencapsulated odors to determine the degree of smell loss ( Doty et al, 1989 ). A Waterless Empirical Taste Test (WETT) was also given to the participant to be completed at home, which includes 27 taste strips with responses (sweet, sour, bitter, salty, brothy, or no taste) to assess taste quality and concentrations ( Doty et al, 2021 ). Once completed at home, both the UPSIT and WETT tests were scored by a researcher over the telephone or email.…”
Section: Methodsmentioning
confidence: 99%